1984
DOI: 10.1021/jm00374a013
|View full text |Cite
|
Sign up to set email alerts
|

[(Arylcarbonyl)oxy]propanolamines. 1. Novel .beta.-blockers with ultrashort duration of action

Abstract: Novel [(arylcarbonyl)oxy]propanolamines were synthesized and investigated as potential ultrashort-acting beta-adrenergic receptor blockers. Many of these analogues exhibited good potency and short duration. The N-ureidoalkyl analogue 85 (ACC-9089) has a potency equal to propranolol and a duration of action of about 21 min in the dog. It has been selected as a candidate for further clinical study. Structure-activity relationships and structure-duration relationships for these new beta-blockers are also discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…This strategy was based on previous studies showing that the presence of bulky chemical groups near metabolically labile ester moieties may slow the rate of ester hydrolysis. 10,11,19,20 In some cases we also shortened the length of the spacer from two carbons to one, forming metomidate rather than etomidate analogs and found that this accelerated metabolism in rat blood. For example, methoxycarbonyl etomidate’s ( I ) metabolic half-life in rat blood was 20 s whereas methoxycarbonyl metomidate’s ( VIII ) half-life was less than 2 s. Similarly, the metabolic half-lives of the ( R )- and ( S )-forms of α-methyl-methoxycarbonyl etomidate ( II & III ) were at least four-fold longer than the respective ( R )- and ( S )-forms of methyl-methoxycarbonyl metomidate ( IX & X ).…”
Section: Discussionmentioning
confidence: 95%
“…This strategy was based on previous studies showing that the presence of bulky chemical groups near metabolically labile ester moieties may slow the rate of ester hydrolysis. 10,11,19,20 In some cases we also shortened the length of the spacer from two carbons to one, forming metomidate rather than etomidate analogs and found that this accelerated metabolism in rat blood. For example, methoxycarbonyl etomidate’s ( I ) metabolic half-life in rat blood was 20 s whereas methoxycarbonyl metomidate’s ( VIII ) half-life was less than 2 s. Similarly, the metabolic half-lives of the ( R )- and ( S )-forms of α-methyl-methoxycarbonyl etomidate ( II & III ) were at least four-fold longer than the respective ( R )- and ( S )-forms of methyl-methoxycarbonyl metomidate ( IX & X ).…”
Section: Discussionmentioning
confidence: 95%
“…It was also shown that the acid metabolites 14 (n ¼ 0, 1) are devoid of b-adrenoceptor activity [102,120]. Somewhat later, following a systematic search of different b-blocker series that contained ester moieties inserted at different positions, esmolol was selected as the best candidate for development [117,[121][122][123].…”
Section: Inactive Metabolite-based Soft Drugsmentioning
confidence: 99%
“…Because relatively early in the study of bblockers, it was found that insertion of an ester moiety between the aromatic ring and the bamino alcohol side chain preserves reasonable b-blocking activity [119,123], a variety of such structures have also been synthesized and investigated. Half-lives in blood and liver suggested that ester hydrolysis is the major pathway for the inactivation of these [(arylcarbonyl)-oxy]propanolamines.…”
Section: Inactive Metabolite-based Soft Drugsmentioning
confidence: 99%
See 2 more Smart Citations